Developing Community Based Maternal and Neonatal Health (MNH) Surveillance: Implications for Monitoring MNH Program in Bangladesh (Bangladesh Journal of Obstetrics & Gynaecology, 2011)
The operation research, “Community Based PNC Study in Bangladesh” was designed with the objective to develop a feasible and sustainable postnatal care package to improving care of newborns and mothers. As a part of monitoring and evaluation of the operation research an independent surveillance system was set up. The objectives of the surveillance were to track the trends of antenatal, delivery and postnatal care over time, provide quarterly feed-back of progress of activities, and evaluate the effectiveness of the PNC package. Through literature review and series of workshops with relevant stakeholders the surveillance method and instruments were developed. Active surveillance was recommended for the two intervention areas. The surveillance had the scope of collecting information on antenatal, delivery, postnatal care of mothers and newborns, birth and death. A set of instruments was developed and pretested to be utilized in the surveillance system. Once a pregnant woman identified was designed to be followed up twice, 10 days before and after the EDD to collect information on antenatal, delivery and postnatal care. The surveillance finding would help to understand the trends of antenatal, delivery and postnatal care. The findings would also be helpful to evaluate the effectiveness of the intervention package. Community based MNH surveillance should be an integral part of maternal and newborn health programs in a country like Bangladesh. Keywords: Surveillance; postnatal care; Bangladesh Bangladesh J Obstet Gynaecol, 2009; Vol. 24(2) : 45-51 DOI: http://dx.doi.org/10.3329/bjog.v24i2.8527